Scientific research, current guidelines in the European Union and ethical issues - Pegiou , Paraskevi; Kountoura, Antonia; Emmanouil , Stavros; Ziagkas , Efthymios (Technium Social Sciences Journal, 2021)
Scientific Research is the main process of evolution of Science. Especially in the Healthcare Sector, the context in which the development of Scientific Research is possible marks both the Legal and the Ethical data of each era. For example, the limits of research, the interventions in Humans, the existence of standards and the continuous control of research data are some of the elements of the ongoing scientific study for the framework within which scientific research can be conducted. In the first part of the present paper, the current in the conduct of Scientific Research in the field of Health at the international level in the field of health are developed through a bibliographic review. The second part of the paper summarizes the rules of the European Union on Scientific Research in Health. Finally, the third part of the work mentions the Ethical issues that have been mentioned in the literature, regarding the conduct of Scientific Research in the Health Sector.